Pengaruh Shalat Terhadap Tingkat Penerimaan Diri Pasien Gagal Ginjal di Klinik Nitipuran - Umi Chudaefah (FAI UMY, 2017)
Pengaruh Shalat Terhadap Tingkat Penerimaan Diri Pasien Gagal Ginjal di Klinik Nitipuran